An improved Random Swapping Thermometer Coding (RSTC) Dynamic Element Matching (DEM) method. Issue 3 (3rd July 2021) - Armuti, Mohammadreza; Bandali, Mehdi; Hashemipour, Omid
ABSTRACT: An improved Random Swapping Thermometer Coding (RSTC) Dynamic Element Matching (DEM) method is presented for Nyquist-rate Digital to Analog converters (DACs). In contrast to the RSTC DEM method, the presented method prevents the Spurious-free dynamic range (SFDR) reduction in DACs in low signal frequencies. Also, while "RSTC with the restricted jumping technique" method is unable to prevent the SFDR reduction in low frequencies for non-full-scale sinusoidal signals, this new method prevents the SFDR reduction in low frequencies for both full-scale and non-full-scale sinusoidal signals. The Fast fourier transform (FFT) analysis for a behavioural model of a 6-Bit thermometer coded DAC at F i n = 0.02 F s ( F i n is the signal frequency and F s is the sample rate) shows 2.1 dB SFDR improvement in comparison to "RSTC with the restricted jumping technique" method. In addition, the presented method achieves a reasonable trade-off between SFDR and Switching activity in comparison to other DEM methods.